2019
DOI: 10.1080/02705060.2019.1588176
|View full text |Cite
|
Sign up to set email alerts
|

An overview of methane emissions in constructed wetlands: how do plants influence methane flux during the wastewater treatment?

Abstract: Plants play an essential role in methane (CH 4) production, transport and release processes of constructed wetlands but as yet there has been no consistent and clear consensus of their impacts on CH 4 emissions. In this study, we used plant presence, species richness, plant species-specificity, and harvesting activity information obtained by reviewing papers published from 1993 to 2018 to elucidate the key factors that drive CH 4 emission from constructed wetlands. Although it was not statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 87 publications
0
6
0
6
Order By: Relevance
“…More generally, nature-based water treatment systems, as well as natural wetlands and WWTPs, are under scrutiny for greenhouse gas contributions associated with methane efflux to the atmosphere. Our results indicate that the unique biomat–water column construct characteristic of open-water wetlands results in methane fluxes (4.5 [0.74–22] mmol m –2 day –1 ) of the same order of magnitude as natural wetlands, such as the Old Woman Creek wetlands in Ohio (mean fluxes ranging between 2.6 and 140 mmol m –2 day –1 ), , as well as other constructed wetlands (median fluxes between 4.5 and 5.6 mmol m –2 day –1 , mean fluxes ranging between 0.22 and 26 mmol m –2 day –1 ) . In comparison to conventional wastewater treatment, we estimate that ∼10 times more methane may be emitted from a shallow open-water wetland (15 [2.5–73] mmol m –3 ) than a municipal WWTP treating the same volume of water (range between ∼0.09 and 1.7 mmol m –3 ) .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…More generally, nature-based water treatment systems, as well as natural wetlands and WWTPs, are under scrutiny for greenhouse gas contributions associated with methane efflux to the atmosphere. Our results indicate that the unique biomat–water column construct characteristic of open-water wetlands results in methane fluxes (4.5 [0.74–22] mmol m –2 day –1 ) of the same order of magnitude as natural wetlands, such as the Old Woman Creek wetlands in Ohio (mean fluxes ranging between 2.6 and 140 mmol m –2 day –1 ), , as well as other constructed wetlands (median fluxes between 4.5 and 5.6 mmol m –2 day –1 , mean fluxes ranging between 0.22 and 26 mmol m –2 day –1 ) . In comparison to conventional wastewater treatment, we estimate that ∼10 times more methane may be emitted from a shallow open-water wetland (15 [2.5–73] mmol m –3 ) than a municipal WWTP treating the same volume of water (range between ∼0.09 and 1.7 mmol m –3 ) .…”
Section: Resultsmentioning
confidence: 77%
“…Our results indicate that the unique biomat− water column construct characteristic of open-water wetlands results in methane fluxes (4.5 [0.74−22] mmol m −2 day −1 ) of the same order of magnitude as natural wetlands, such as the Old Woman Creek wetlands in Ohio (mean fluxes ranging between 2.6 and 140 mmol m −2 day −1 ), 108,109 as well as other constructed wetlands (median fluxes between 4.5 and 5.6 mmol m −2 day −1 , 110 mean fluxes ranging between 0.22 and 26 mmol m −2 day −1 ). 111 In comparison to conventional wastewater treatment, we estimate that ∼10 times more methane may be emitted from a shallow open-water wetland (15 [2.5−73] mmol m −3 ) than a municipal WWTP treating the same volume of water (range between ∼0.09 and 1.7 mmol m −3 ). 112 However, our insights demonstrate that bacteria that are dependent on methane produced in these environments can also play a beneficial role in attenuating pharmaceutical compounds and perhaps nitrogen.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Although not statistically significant, CH 4 fluxes were found slightly higher in vegetated constructed wetlands than unvegetated constructed wetlands with some species such as Typha latifolia and C. papyrus generated lower methane fluxes (Xu, Li, Wang, Kong, & Yu, 2019).…”
Section: Ghg Emissions From Wrrfsmentioning
confidence: 92%
“…Firstly, some plants have been found to suppress CH 4 fluxes (Table 4). A monitoring study by Bateganya et al (2015) found that planting Cyperus papyrus was more effective for the suppression of CH 4 fluxes regardless of the CW types, due to the extensive belowground rhizome network facilitating O 2 transfer (Xu et al, 2019;Zhang et al, 2021a). Cyperus alternifolius is a ciliate with large root surface areas and root lengths of approximately 20 cm, providing them with the capacity to reach the bottom of CWs and release high amounts of root O 2 , leading to a more extensive aerobic environment (Chen et al, 2020c).…”
Section: Plant Species Selectionmentioning
confidence: 99%
“…Overall, the contribution of plants to CH 4 emissions remains unclear. For example, Phragmites australis has an extensive rhizome system that typically penetrates substrate depths of 0.6-1.0 m, and has been reported to effectively reduce CH 4 fluxes (Xu et al, 2019), while other studies have reported that Phragmites australis possesses highly developed aerenchyma that allow more efficient gas transfer and increase CH 4 emissions (Sheng et al, 2015;Chen et al, 2020c). Moreover, some studies have proposed that certain plant species has no overall impact on CW CH 4 emissions (Han et al, 2019;Maucieri et al, 2019).…”
Section: Plant Species Selectionmentioning
confidence: 99%